PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKN MELALUI METODE BERMAIN PERAN DI KELAS VI SDN 06 BUKIT GADANG - MARYULIS MARYULIS (STKIP Pesisir Selatan, 2019)
The lack of active and low learning outcomes of Citizenship Education in the process of formulating Pancasila as the basis of the country due to the use of learning methods by conventional teachers and are less attractive to students, making student learning outcomes low. This type of research is a class action research (class action research), research using qualitative and quantitative approaches. The research procedure consists of stages: planning, implementation phase, observation phase, and reflection phase. The research data were obtained by writing tests and using observation sheets. The subjects were grade VI students of SDN 06 Bukit Gadang Talawi Subdistrict, Sawahlunto City in the first semester of 2017/2018 academic year as many as 20 people. The results showed the role playing method (Role Playing) could increase learning outcomes Citizenship Education in the material formulation process of Pancasila as the basis of the state in class VI SDN 06 Bukit gadang Talawi District Sawahlunto with completeness in Cycle I completeness 70% student completeness Teacher activity in teaching cycle I 74.5% implemented and students active cycle I 73%. After being reflected on weakness in cycle I an increase in cycle II was 88% students completeness, teacher activity increased to 94% and students were active 91%. From the research analysis it can be concluded that through the role playing method (Role Playing) can improve student learning outcomes in PKN learning in class VI SDN 06 Bukit gadang.